Toripalimab plus chemotherapy for metastatic muscle-invasive bladder cancer with a high tumor proportion score: a case report - Ning, Wei; Chang, Pengkang; Zheng, Ji; Chen, Wei (Frontiers in Immunology, 2024)
BackgroundRadical cystectomy (RC) combined with pelvic lymph node dissection (PLND) is the standard treatment for muscle-invasive bladder cancer (MIBC). For metastatic MIBC patients, platinum-based chemotherapy remains the first choice treatment. However, approximately 50% of patients with metastatic MIBC are ineligible for platinum-based adjuvant chemotherapy because of impaired renal function. In programmed death ligand 1 (PD-L1)-positive patients who cannot tolerate platinum-based chemotherapy, immunotherapy is recommended. Thus, a major shift is taking place in the treatment of patients with metastatic MIBC. There is currently much interest in the use of chemotherapy combined with immunotherapy and maintenance immunotherapy for the treatment of metastatic MIBC.Case presentationOne patient with metastatic MIBC exhibited promising progression-free survival (PFS) and safety and had good renal function after RC and toripalimab combined with chemotherapy plus toripalimab maintenance therapy.ConclusionRC plus adjuvant therapy (toripalimab combined with chemotherapy) plus toripalimab maintenance therapy is a potential treatment option for metastatic MIBC patients who want to prolong their life. Moreover, a high tumor proportion score (TPS) of PD-L1 expression as well as CDKN2A and TP53 mutation levels may predict immunotherapy efficacy and patient prognosis.